Effectiveness evaluation method on construction of active distribution network based on public service value model. (October 2019) - Zhou, Y J; Fang, R C; Xu, J Y; Wang, Y X; Lei, H; He, J F
Abstract: Evaluating the construction effectiveness of active distribution network is the key point of coordinated development of distribution network. At present, effectiveness evaluation on the distribution network in domestic only focuses on output performance while leaves out of consideration of utilization efficiency of investment. Therefore, this paper presents a kind of effectiveness evaluation method for construction and updating of the active distribution network based on public service value model which could make an overall evaluation in two dimensions of output performance and cost efficiency. The evaluation results are comprehensively analyzed on the four quadrant diagram, and the evaluation conclusions and suggestions are put forward according to the quadrant of the evaluation objects. Finally, it verifies this evaluation method is scientific, reasonable and feasible in guiding construction investment of the power grid by applying the method in evaluating construction effectiveness of distribution networks in some areas of Hubei Province in China.